Font and Colour Attributes as Manipulated in Mass Media Texts: Psycholinguistic Implications - Makaruk, Larysa (Lesya Ukrainka Volyn National University, 2020)
This paper is aimed to analyse font and colour as non-verbal and paralingual components which have the capacity to influence and manipulate recipients of a message. On the basis of an extensive body of illustrative material, it has been established that by the use of colour variation, a single text fragment may be interpreted in several different ways, and may also be perceived differently by men and by women. It is demonstrated that colour and font characteristics are not exclusively graphic shells whose function is merely to record an oral statement in writing. They are semantically significant and multifunctional. It has been determined that font and colour are form-creating elements, which make possible the graphic reproduction of objects in everyday use, objects relating to reality and actuality. Variation in font and colour enable us to hypothesize that the mass media communication space is now characterized by a type of linguistic play utilizing these traits so as to render possible the projection of multiple-reading promotional texts. They also permit an economy in terms of space because of the fact that font techniques can perform formative and content functions simultaneously. Based on an experiment involving 60 participants, 30 of whom were male and 30 female, it was found that the information encoded in colour and font graphics shells is not difficult to perceive and to decipher. However, the survey found that women are more likely to perceive that information, although the difference in perception is not striking. When asked whether a sample of illustrative material stirred an appetite by using stylized fonts consisting of foods to convey a food-related message, 74 % of men and 37% of women in both articles answered in the positive, which in our study confirms the claim that food advertising promotes appetite arousal. The study also showed that most women who read the information perceive it holistically–their attention is not attracted solely by verbal and nonverbal components. On the other hand, only half of the men surveyed saw it as a whole, and almost a third of them initially noticed the verbal components first. Most participants in the experiment claimed that it took them from 5 to 10 seconds to realize that a single message could be read in several different ways. The participants who took part confirm that a single text string can be interpreted in multiple ways due to the font and colour attributes that are utilized in forming them.
Keywords: font; colour; multimodal; verbal; non-verbal; play